OPTIMALISASI JENIS DAN DOSIS PUPUK KANDANG UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica juncea L.) - Jadi Jadi; Primadiyanti Arsela; Ardaniah Ardaniah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
Green mustard is a leafy horticultural crop whose growth is strongly influenced by nutrient availability during the vegetative stage. This study aimed to analyze the effects of manure type and application rate on the growth and yield of green mustard and to determine the optimal treatment. The experiment was arranged in a two-factor Randomized Complete Block Design (RCBD), consisting of manure type (chicken, cattle, and goat manure) and manure rate (0, 12.5, 25, 37.5, and 50 g per polybag), with four replications. Observed parameters included plant height, number of leaves, leaf width, and fresh weight. Data were analyzed using analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test at the 5% level. The results showed that manure type and application rate had significant to highly significant effects on all observed parameters, with chicken manure at a rate of 37.5 g per polybag producing the best vegetative growth. These findings indicate that chicken manure applied at an optimal rate can effectively supply nutrients to support the growth of green mustard.